2023
DOI: 10.3390/jof9050583
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Infections in the ICU during the COVID-19 Pandemic in Mexico

Abstract: Background: Invasive Fungal Infections (IFI) are emergent complications of COVID-19. In this study, we aim to describe the prevalence, related factors, and outcomes of IFI in critical COVID-19 patients. Methods: We conducted a nested case–control study of all COVID-19 patients in the intensive care unit (ICU) who developed any IFI and matched age and sex controls for comparison (1:1) to evaluate IFI-related factors. Descriptive and comparative analyses were made, and the risk factors for IFI were compared vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
0
1
Order By: Relevance
“…The prevalence rate for CAPA cases estimated in this study is lower compared to previous series including those reported in our country and worldwide 22,23 . Reports in Mexico have estimated a prevalence of CAPA between 5.6% 24 and 19.3% 23 . The lower prevalence in this study might be explained by two reasons, one is the type of diagnostic methods used.…”
Section: Discussioncontrasting
confidence: 84%
“…The prevalence rate for CAPA cases estimated in this study is lower compared to previous series including those reported in our country and worldwide 22,23 . Reports in Mexico have estimated a prevalence of CAPA between 5.6% 24 and 19.3% 23 . The lower prevalence in this study might be explained by two reasons, one is the type of diagnostic methods used.…”
Section: Discussioncontrasting
confidence: 84%